Molecular relaxation processes in genomic DNA from leaf tissues: A surface-enhanced Raman spectroscopic study. Issue 4 (2011) - Muntean, Cristina M.; Bratu, Ioan; Leopold, Nicolae
Abstract : In this work the SERS total half bandwidths of six genomic DNAs from ex vitro-grown apple leaf tissues ( Malus domestica Borkh., Fam. Rosaceae, cvs. Rebra, Goldrush, Florina, Romus 4, and the rootstocks M26, M9) and of five genomic DNAs from in vitro grown plants of Arnica montana (L.), Fam. Compositae, Astragalus peterfii (Jáv.), Fam. Fabaceae, strawberry (Duch.), Fam. Rosaceae, carnation ( Dianthus caryophyllus L.), Fam. Caryophyllaceae, and Kalanchoe x hybrida, Fam. Crassulaceae, respectively, have been measured. We have shown that surface-enhanced Raman scattering can be used to study the fast subpicosecond dynamics of DNA in the proximity of a metallic surface. The dependencies of the total half bandwidths and of the global relaxation times, on DNA molecular subgroup structure and on the type of genomic DNA, are reported. It is shown that changes in the subpicosecond surface dynamics of molecular subgroups in genomic DNAs from leaf tissues can be monitored with surface-enhanced Raman spectroscopy . In our study, the full widths at half-maximum (FWHMs) for the SERS bands of genomic DNAs from different leaf tissues, are typically in the wavenumber range from 15 to 30 cm –1 for data set 1 and from 13 to 42 cm –1 for data set 2. Besides, it can be observed that molecular relaxation processes studied in this work, have a global relaxation time smaller than 0.71 ps and larger than 0.35 ps (data set 1) and also varying between 0.25–0.82 ps for data set 2. A comparison between different ranges of FT-Raman and SERS band parameters, respectively, of DNA extracted from leaf tissues is given. We have found that the bands of DNA from Florina cultivar and Kalanchoe leaves, respectively, are suitable for the study of dynamical behaviour of molecular subgroups in nucleic acids extracted from different leaf tissues.